Association of Lipoprotein Lipase Hind III and Ser 447 Ter Polymorphisms With Dyslipidemia in Asian Indians - Radha, Venkatesan; Mohan, Viswanathan; Vidya, Ramprakash; Ashok, Ayyappa K.; Deepa, Raj; Mathias, Rasika A. (The American journal of cardiology, 2006)
Studies have shown an association between the lipoprotein lipase gene and dyslipidemia and atherosclerosis in some populations. The aim of this study was to investigate the association between the common lipoprotein lipase HindIII (T-G) and Ser447Ter (C-G) polymorphisms with dyslipidemia in Asian Indians, who are known to have very high rates of premature coronary artery disease. A total of 1,015 subjects, comprising 550 normal glucose-tolerant subjects and 465 patients with type 2 diabetes, were randomly selected from the Chennai Urban Rural Epidemiology Study. The total serum cholesterol, high-density lipoprotein (HDL) cholesterol, and serum triglyceride levels were assayed using enzymatic methods. Low-density lipoprotein cholesterol was calculated using the Friedewald formula. Genotyping was done using the polymerase chain reaction-restriction fragment length polymorphism method. A significant association was found between the H+ allele of HindIII with low HDL cholesterol and elevated triglyceride levels. The Ser allele of Ser447Ter was also strongly associated with low HDL cholesterol levels. No association was found between the H+ allele and Ser Allele with the total or low-density lipoprotein cholesterol levels. Group-wise haplotype frequencies were generated using the expectation-maximization algorithm to detect differences in overall haplotype frequency profiles between the case-control groups. The haplotype analysis showed that the H+ Ser and H− Ter were the “high-risk” and “low-risk” haplotypes for low HDL cholesterol and elevated triglyceride levels, respectively. In conclusion, the H+ Ser haplotype of the lipoprotein lipase gene was associated with low HDL cholesterol levels and hypertriglyceridemia in Asian Indians.